Dr google is here to stay but health care professionals are still valued: An analysis of health care consumers' internet navigation support preferences - Lee, K.; Hoti, K.; Hughes, J.; Emmerton, Lynne (Journal of Medical Internet Research, 2017)
Background: The Internet offers great opportunities for consumers to be informed about their health. However, concerns have been raised regarding its impact on the traditional health consumer-health professional relationship. Our recent survey of 400 Australian adults identified that over half of consumers required some form of navigational support in locating appropriate Web-based health information. We propose that support provided by health professionals would be preferred by consumers; this preference is regardless of whether consumers have a need for navigational support. Secondary analysis of the survey dataset is presented here to quantify consumer-reported support preferences and barriers when navigating Web-based health information. Objective: We aimed to quantitatively identify consumers' support preferences for locating Web-based health information and their barriers when navigating Web-based health information. We also aimed to compare such preferences and barriers between consumers identified as needing and not needing support when locating Web-based health information. Methods: Chi-square ( 2 ) tests identified whether each listed support preference differed between subgroups of consumers classified as needing (n=205, 51.3%) or not needing (n=195, 48.8%) navigational support; degree of association, via phi coefficient (f) tests, were also considered to ascertain the likely practical significance of any differences. This was repeated for each listed barrier. Free-text responses regarding additional support preferences were descriptively analyzed and compared with the quantitative findings to provide a richer understanding of desired support for health information searches. Results: Of the 400 respondents, the most preferred mode of navigational support was involvement of health professionals; this was reported by participants identified as needing and not needing navigational support. While there was a significant difference between groups, the degree of association was small ( 2 1 [N=400]=13.2; P < .001; f=.18). Qualitative data from the free-text responses supported consumers' desire for health professional involvement. The two most commonly reported barriers when navigating desired Web-based health information were (1) volume of available information and (2) inconsistency of information between sources; these were reported by participants with and without a need for navigational support. While participants identified with a need for navigational support were more likely to report volume ( 2 1 [N=387]= 4.40; P=.04; f=.11) and inconsistency of information ( 2 1 [N=387]= 16.10, P < .001, f=.20) as barriers, the degrees of association were small to moderate. Conclusions: Despite concerns in the literature that the popularity of the Internet could compromise the health consumer-health professional relationship, our findings suggest the contrary. Our findings showed that health professionals were found to be the most commonly preferred mode of navigational support, even among consumers classified as not needing navigational support. Further research into how health professionals could assist consumers with Web-based health information seeking could strengthen the health consumer-health professional relationship amidst the growing use of "Dr Google.".